Oral manifestation in patient with systemic lupus erythematosus: Manifestasi oral pada pasien sistemik lupus eritematosus - Fanni Kusuma Djati; Reynaldo Binsar Hutajulu; Ayu Intan Nur Anissa; Bestaria Sani Kuncoro; Violentri Multri (Makassar Dental Journal PDGI Makassar, 2026)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that can affect various organs, including the oral cavity. Oral manifestations such as ulcers, candidiasis, cheilitis, and lichen planus-like lesions often reflect the activity of certain systemic diseases. A 26-year-old woman with a history of SLE, lu-pus nephritis, severe anaemia, and suspected neuropsychiatric lupus presented with complaints of fatigue, dizziness, leg swelling, pain when swallowing, re-current seizures, and oral discomfort. Intraoral examination revealed lichen planus-like lesions on the anterior buccal mucosa, ulcers on the posterior buccal mucosa, traumatic ulcers on the lateral tongue due to seizures, candidiasis on the dorsum of the tongue, and exfoliative cheilitis on the lips. Laboratory results showed severe anaemia, leukocytosis with lymphopenia, hypocalcaemia, and renal dysfunction. Treatment included oral hygiene education, use of a soft-bristled toothbrush, tongue cleaning with sterile gauze, nutritional counselling, and coordination with the Department of Internal Medicine for systemic monito-ring. Invasive procedures were avoided due to the risk of bleeding and infection. It was concluded that oral manifestations in SLE vary and can be indicators of systemic conditions. Dentists play an important role in early detection, supportive therapy, and multidisciplinary collaboration to improve patients' quality of life.